Decision makers consider all options in choice triplets - Douglas G. Lee (PLoS ONE, 2025)
Most contemporary decision-making research focuses on choices between only two alternative options, in spite of the fact that most real-world decisions involve more than two options. Beyond this practical point, multi-option decisions are also important from a theoretical perspective. Experimental and computational studies have demonstrated that the composition of a set of choice options has predictable effects on choice outcomes. Specifically, with more options available to choose from, responses are slower and more stochastic. This effect is amplified when the values of the options (including the worst option in the set) are more similar to each other. In this study, we provide further evidence of these known effects. We also provide evidence that metacognitive factors such as feelings of confidence in the response or mental effort exertion during deliberation show similar effects as the cognitive factors (consistency between choices and value estimates, response speed). Finally, we provide novel evidence that value estimates are refined during deliberation for all options in choice triplets, similar to what has previously been show for choice pairs.